Relationships, health, and stress: Validation of a relationship sense of coherence measure. Issue 1 (23rd November 2020) - Davis, Bret A.; Shrout, M. Rosie; Evans, William P.; Weigel, Daniel J.
Abstract: Although all romantic relationships experience stress, some thrive when faced with adversity while others are unable to manage the inevitable relationship ups and downs. Rather than seeing stress as a risk factor, this study applied a Salutogenic framework, which posits that stress is a naturally occurring and potentially beneficial part of relationships, to develop a new measure of relationship health and well‐being. In Study 1, we created and tested a self‐report Relationship Sense of Coherence (RSOC) scale. Study 2 demonstrated evidence of convergent reliability for the RSOC. In Study 3, we tested the RSOC in a two‐wave sample of romantically‐involved individuals with a chronic health condition. Guidelines for use and implications for future research are discussed.